BEYOND HUMAN COMMUNICATION: THE ARTIFICIAL INTELLIGENCE PHENOMENON IN THE PERSPECTIVE OF COMMUNICATION THEORY - Prahastiwi Utari; Pramana Pramana; Amelia Ramadhani (Master of Communication Science Program, Universitas Diponegoro, 2024)
The study of the Artificial Intelligence (AI) phenomenon has developed rapidly in recent years by placing various multi-disciplinary perspectives including Communication. The question then arises, how to study the AI phenomenon with a Communication approach? What kind of communication theories can be used to explain the AI phenomenon? Can the existing perspective of communication theory, which emphasizes the notion of communication as an interaction in which two communicators, using some medium of communication, move towards a better understanding of each other through the exchange of messages, still be used? Is the communication theory domain in terms of elements, levels and contexts of communication still relevant to studying the AI phenomenon? Is there a possibility of developing a new group of theories in studying AI phenomena?. This paper will provide an inspiring perspective on the development of a group of communication theories called